Adult cystic lymphangioma in the inner quadrant of the breast—Rare location for a rare disease: A case report. (2016) - Rusdianto, Eve; Murray, Mary; Davis, Jennifer; Caveny, Anne
Highlights: Adult cystic breast lymphangioma is an extremely rare condition, especially in the inner upper quadrant of the breast. Cystic lymphangiomas of the breast are benign lymphatic malformations. Cystic lymphangiomas of the breast are typically located in the upper outer quadrant, the tail of Spence, and subareolar area. Surgical excision with histopathology examination provides definitive diagnosis of cystic lymphangioma. Complete surgical excision remains the most effective treatment modality for adult cystic lymphangioma of the breast. Abstract: Introduction: Adult cystic lymphangioma of the breast is extremely rare, especially in the breast's upper, inner quadrant. Review of literature is discussed, including etiology, differential diagnosis, workup, and treatment of the disease. Presentation of case: A 20-year-old female presented with a recurrent left breast cyst. Previous aspirations showed no malignancy. Ultrasonography showed a lobulated anechoic lesion with internal debris and thin septations. The patient then underwent a lumpectomy of the left breast cyst, and pathology showed lymphangioma. Discussion: Cystic lymphangiomas of the breast are benign lymphatic malformations. Consistent with the main drainage pattern of the breast, cystic lymphangiomas are typically located in the upper, outer quadrant, tail of Spence, and subareolar area. Radiologic evaluation may include ultrasound, mammogram, and MRI. FNA cytology and core biopsy assist in the diagnosis of breast lymphangioma. Although different treatment options exist, complete surgical excision remains the most effective treatment modality for adult cystic lymphangioma of the breast. Conclusion: Breast cystic lymphangioma is an extremely rare condition, especially in the upper, inner quadrant of the breast. The patient had multiple recurrences of the lesion after fine needle aspirations. Proper index of suspicion, prompt diagnosis, and definitive treatment is necessary to prevent recurrence and complications.